Supernatural - Mills, John, Sir; Sidaway, Ashley; Sidaway, Robert; Sellar, Maurice (Herts : Screen Entertainment, 1991)
British films about the supernatural have always been popular. In this programme many memorable scenes of true suspense and terror are illustrated, demonstrating how effective good supernatural stories can be when translated to thescreen.
Fantasy takes a look at some entertaining British fantasy films where the limits of the imagination are explored and brought to life on the big screen through special effects and the vivid imagination of British film-makers.
Narrated by John Mills.
Keywords: Supernatural in motion pictures; Fantasy -- Drama; Motion pictures -- United Kingdom -- History